Chinese Fatherhood, Gender and Family : Father Mission - Liong, Mario (Palgrave Macmillan Studies in Family and Intimate Life, 2017)
This book is about how Chinese men make sense of and practise fatherhood within the context of changing gender conventions and socio-cultural conditions. Liong analyses data from participant observations at a men's centre, focus groups, and in-depth interviews, to assess the subjective experience and identities of Chinese fathers in Hong Kong, from a gender perspective. His findings show that economic provision, education, and marriage are the three "natural" and "normal" domains of paternity. Not being able to fulfil these requirements is a threat to fathers' masculinity, yet is also an opportunity for fathers to reflect upon these accepted conventions. In order to compensate, these men typically develop a closer and more caring relationship with their children, however these fathers still struggle with feelings of inferiority.- Resumé vydavatel